The use of seamless learning strategy on student vocabullary mastery - Muhammad Berlin Al Ausi; Muhammad Luthfi Abdillah (JURNAL PENDIDIKAN, 2020)
This study aims to see empirical evidence of the effect of unlimited learning on students’ vocabulary mastery. Researchers used experiments in class 1 MTs Darussalam Gapluk Purwosari Bojonegoro. It aims to increase students’ awareness by expanding their room from home and school to their everyday lives. Seamless learning allows for continuous learning experiences in a number of environments, such as school or home, while seamless learning is spread across multiple environments. Seamless learning is a flawless network where learning takes place anywhere and anytime. Some of the benefits of using a seamless approach include: 1) students can study classes and time without limits 2) students can study at any time, and anywhere 3) integrated learning between formal and non-formal education. Based on the outcome of the estimation of post-test, the average post-test score was 82.6667, while the pre-test average was 52000. This means that the average post-test is 52000. The score is higher than the pre-test.